Report of Jacobsen syndrome with a mild facial dysmorphism, severe hearing impairment and thrombocytopenia - DIRSĖ, Vaidas; CIMBALISTIENĖ, Loreta; KASNAUSKIENĖ, Jūratė; KUČINSKAS, Vaidutis (Acta medica Lituanica, 2012)
Background. Jacobsen syndrome is a rare syndrome with variable phenotypic expression depending on the breakpoints and the size of 11q deletion. There is presented a wide range of phenotypes of varying severity. Detailed molecular cytogenetic analysis leads to better knowledge of genetic causes of this syndrome. Materials and methods. Molecular cytogenetic analysis using subtelomeric FISH and array CGH was performed for a patient with Jacobsen syndrome. Results. Subtelomeric FISH detected an unbalanced translocation 46,XY,der(11)t(11;13)(q24.2;p11.2) of our patient. Array CGH analysis revealed a 13.95 Mb terminal deletion of the 11q23.3 region (breakpoint positions 120, 505, 418–134, 452, 384, NCBI build 36). FISH and GTG banding analysis identified a balanced translocation 46,XX,t(11;13) (q24.2;p11.2) of patient’s mother. Conclusions. The results of this case report suggest the need of combining both molecular cytogenetic methods: array CGH and FISH for precise analysis of patients with Jacobsen syndrome.